Attenuation in Superconducting Circular Waveguides - Yeap, K. H.; Ong, S. S.; Nisar, H.; Lai, K. C.; Ng, C. A. (Advanced Electromagnetics, 2016)
We present an analysis on wave propagation in superconducting circular waveguides. In order to account for the presence of quasiparticles in the intragap states of a superconductor, we employ the characteristic equation derived from the extended Mattis-Bardeen theory to compute the values of the complex conductivity. To calculate the attenuation in a circular waveguide, the tangential fields at the boundary of the wall are first matched with the electrical properties (which includes the complex conductivity) of the wall material. The matching of fields with the electrical properties results in a set of transcendental equations which is able to accurately describe the propagation constant of the fields. Our results show that although the attenuation in the superconducting waveguide above cutoff (but below the gap frequency) is finite, it is considerably lower than that in a normal waveguide. Above the gap frequency, however, the attenuation in the superconducting waveguide increases sharply. The attenuation eventually surpasses that in a normal waveguide. As frequency increases above the gap frequency, Cooper pairs break into quasiparticles. Hence, we attribute the sharp rise in attenuation to the increase in random collision of the quasiparticles with the lattice structure.